2001
DOI: 10.1016/s0014-5793(01)02457-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, aging and longevity in Drosophila melanogaster

Abstract: Free radicals produced during normal metabolism cause damage to macromolecules. The free radical theory of aging proposes that the organism is unable to repair all of them and that, with time, unrepaired damages accumulate and put the organism at risk: in other words, free radicals provoke aging and death. This article reviews both the results of adding antioxidants to food on longevity in Drosophila melanogaster, as well as the studies on antioxidant enzymes (inactivation in vivo, null mutants, overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 41 publications
4
41
0
5
Order By: Relevance
“…Le Rohellec and Le Bourg (2009) thus reported some positive effects of suppressing live yeast on longevity, contrarily to previous studies of the same laboratory using other DR methods (Le Bourg and Médioni 1991;Le Bourg and Minois 1996), and on behavioral aging, but they also showed that DR increased frailty. Thus, suppressing live yeast has both positive and negative effects.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Le Rohellec and Le Bourg (2009) thus reported some positive effects of suppressing live yeast on longevity, contrarily to previous studies of the same laboratory using other DR methods (Le Bourg and Médioni 1991;Le Bourg and Minois 1996), and on behavioral aging, but they also showed that DR increased frailty. Thus, suppressing live yeast has both positive and negative effects.…”
Section: Introductionsupporting
confidence: 52%
“…Contrasting effects of DR on longevity have been reported in D. melanogaster. Intermittent feeding did not increase longevity (Kopec 1928;Le Bourg and Médioni 1991). Dilution of a rearing medium containing dry yeast had no effect on longevity (David et al 1971;Soh et al 2008) or increased it (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such compounds might also have adverse secondary effects that would limit their clinical use in the treatment of aging. As discussed in a review by Le Bourg, the potential secondary effects of antioxidants have been evaluated in a few studies (LeBourg 2001). To date, anti-aging studies have not systematically evaluated the secondary adverse effects of potential anti-aging compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the powerful ROS neutralizers coenzyme Q 10 and alpha-lipoic acid (ALA) fail to extend lifespan of mice (Lee et al 2004). Such contradictory results with even negative effects on longevity are also described for a variety of antioxidant compounds tested in the fruit fly, as summarized in Le Bourg (2001). Among the popular antioxidants, Driver and Georgeou (2003) discuss the variability associated with the effects of vitamin E on Drosophila lifespan.…”
Section: Antioxidantsmentioning
confidence: 99%